Genome-wide characterization of AINTEGUMENTA-LIKE family in Medicago truncatula reveals the significant roles of AINTEGUMENTAs in leaf growth - Wang, Xiao; Zhang, Juanjuan; Zhang, Jing; Zhou, Chuanen; Han, Lu (Frontiers in Plant Science, 2022)
AINTEGUMENTA-LIKE (AIL) transcription factors are widely studied and play crucial roles in plant growth and development. However, the functions of AIL family in legume species are largely unknown. In this study, 11 MtAIL genes were identified in the model legume Medicago truncatula, of which four of them are MtANTs. In situ analysis showed that MtANT1 was highly expressed in the shoot apical meristem (SAM) and leaf primordium. Characterization of mtant1 mtant2 mtant3 mtant4 quadruple mutants and MtANT1-overexpressing plants revealed that MtANTs were not only necessary but also sufficient for the regulation of leaf size, indicating they mainly function in the regulation of cell proliferation during secondary morphogenesis of leaves in M. truncatula. Taken together, this study systematically analyzed the MtAIL family at the genome-wide level and the functions of MtANTs in leaf growth, which provides the potential application for promoting the biomass of legume forages.